Dynamics of integron structures across a wastewater network – Implications to resistance gene transfer. (1st November 2021) - Quintela-Baluja, Marcos; Frigon, Dominic; Abouelnaga, M.; Jobling, Kelly; Romalde, Jesús L.; Gomez Lopez, Mariano; Graham, David W.
Highlights: Prevalence and types of integrons vary widely across a wastewater network. Human-impacted class 1 integrons carrying ARGs dominate, but are highest in hospital wastewater. New qPCR assays are reported that segregate "anthropogenic" class 1 integrons that carry ARGs (aint1) vs empty structures (eaint1). Recycled activated sludge has triple the "empty structures" per integron relative to WWTP liquid effluents. Integron dynamics help identify wastewater compartments with elevated ARG transfer. Abstract: Class 1 and other integrons are common in wastewater networks, often being associated with antibiotic resistance genes (ARGs). However, the importance of different integron structures in ARG transfer within wastewater systems has only been implied, especially between community and hospital sources, among wastewater treatment plant compartments, and in receiving waters. This uncertainty is partly because current clinical class 1 integron qPCR assays (i.e., that target human-impacted structures, i.e., clintI1 ) poorly delineate clintI1 from non-impacted class 1 integron structures. They also say nothing about their ARG content. To fill these technical gaps, new real-time qPCR assays were developed for "impacted" class 1 structures (called aint1 ; i.e., a nthropogenic class 1 integrons) and empty aint1 structures (i.e., carry no ARGs; called eaint1 ). The new assays and other integron assays then were used to examine integron dynamics across a wastewater network. 16S metagenomic sequencing also was performed to characterise associated microbiomes. aint1 abundances per bacterial cell were about 10 times greater in hospital wastewaters compared with other compartments, suggesting aint1 enrichment with ARGs in hospital sources. Conversely, the relative abundance of eaint1 structures were over double in recycled activated sludge compared with other compartments, except receiving waters (RAS; ∼30% of RAS class 1 structures did not carry ARGs). Microbiome analysis showed that human-associated bacterial taxa with mobile integrons also differed in RAS and river sediments. Further, class 1 integrons in RAS bacteria appear to have released ARGs, whereas hospital bacteria have accumulated ARGs. Results show that quantifying integron dynamics can help explain where ARG transfer occurs in wastewater networks, and should be considered in future studies on antibiotic resistance in the environment. Graphical abstract: Image, graphical abstract